2022
DOI: 10.3390/life12020191
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Aortic Aneurysm Formation with a Focus on Vascular Smooth Muscle Cells

Abstract: Abdominal aortic aneurysm (AAA) is a lethal degenerative vascular disease that affects, mostly, the elder population, with a high mortality rate (>80%) upon rupture. It features a dilation of the aortic diameter to larger than 30 mm or more than 50%. Diverse pathological processes are involved in the development of AAA, including aortic wall inflammation, elastin breakdown, oxidative stress, smooth muscle cell (SMC) phenotypic switching and dysfunction, and extracellular matrix degradation. With open surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 162 publications
1
27
0
Order By: Relevance
“…It is widely acknowledged that inflammatory mediators contribute to phenotypic and functional alterations in AoSMCs during AAA development (reviewed in 41 ). Stress-triggered c ATM transcription would thus work as a signal for activating survival pathways (like BCL2 ) by fine-tuning ATM expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely acknowledged that inflammatory mediators contribute to phenotypic and functional alterations in AoSMCs during AAA development (reviewed in 41 ). Stress-triggered c ATM transcription would thus work as a signal for activating survival pathways (like BCL2 ) by fine-tuning ATM expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…of small aneurysms continue to expand to rupture and are expected to be related to multiple factors after surgery [13, 14]. In the development of abdominal aortic aneurysm, VSMC phenotype function conversion and dysfunction, the VSMC phenotype can be converted into macrophage-like cells during the development of abdominal aortic aneurysm, and the phenotype conversion is correlated with arterial calcification and arteriosclerosis density [9].…”
Section: Discussionmentioning
confidence: 99%
“…VSMCs express proteolytic enzymes to degrade the aortic extracellular matrix. Apoptosis of VMSCs is another important factor in the development of AAA [9]. Studies have shown that knockdown of Angptl2 can inhibit the proliferation, migration and invasion of VSMCs [10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, elective stable abdominal aortic aneurysms (eAAAs) can be fatal. In spite of extensive literature on the pathogenesis, evolution, and rupture of AAA (13)(14)(15), prevention or suppression of AAA in a clinical setting still remains an unanswered question.…”
Section: Introductionmentioning
confidence: 99%